Tingkat Kompetensi Interpersonal Sales Promotion Girl (SPG) : Kajian Deskriptif - Dartina, Vina; Fahriza, Irfan; Alfaiz, Alfaiz; Julius, Andre (Universitas Mathla'ul Anwar Banten, 2023)
Communication is important in social interaction, even for promotion and sales. The purpose of this research is to reveal the Eta Agency Pro Comm sales promotion girl's interpersonal competence, openness, empathy, support, positivity, and Equality. Data was collected through Interpersonal Communication Scale (ICS) with a high-reliability value of 0,95. The sample was taken based on Purposive Random Sampling, with 58 respondents of sales promotion girls. This research found that every aspect of Interpersonal Communication of Sales Promotion Girls at the Competence level. Only Support communication there are 25 (43,10%) in Very Competence. İn another aspect below of that. This research suggests that communication is a combination in every aspect and always reciprocal in every social interaction.